Impact of tocilizumab therapy on immunological parameters in patients with rheumatoid arthritis - Anastasia Sergeyevna Avdeyeva; E N Aleksandrova; E Yu Panasyuk; A A Novikov; M V Cherkasova; E L Nasonov (Научно-практическая ревматология)
Objective: to evaluate the impact of tocilizumab (TCZ) therapy on the level of acute-phase indicators, autoantibodies, and immunoglobulins (Ig) G, M, and A after 2, 4, 8, 12, and 24 weeks as compared to the clinical efficacy of TCZ using DAS 28, SDAI, and CDAI scores and to reveal the immunological predictors of effective TCZ therapy. Subjects and methods. Forty-two patients with rheumatoid arthritis (RA) who had received 6 TCZ infusions in an intravenous dose of 8 mg/kg at a 4-week interval during stable therapy with disease-modifying antirheumatic drugs (DMARDs) and glucocorticosteroids were examined. Erythrocyte sedimentation rate (ESR) was determined by the Westergren method; the levels of C-reactive protein (CRP), IgM rheumatoid factor (RF), IgG, IgM, and IgA were measured by a nephelometric method; the content of anti-cyclic citrullinated peptide (anti-CCP) antibodies was estimated by an electrochemiluminescence technique. Results. In the respondents to TCZ therapy, the baseline Me values [25 th; 75 th percentiles] were 6.44 (5.87; 7.04) for DAS 28; 41.5 (32; 53) for SDAI; and 36.4 (19.2; 62.7) mg for CRP; 262.0 (95.3; 663.0) IU/l for IgM RF; 342.5 (106.9; 789.9) IU/ml for IgA RF; 366.8 (76.9; 500.0) for anti-CCP antibodies; 770.5 (190.7; 2393.1) IU/ml for anti-modified citrullinated vimentin (anti-MCV) antibodies; 16.1 (12.9; 21.1) g/l for IgG; 2.07 (1.68; 2.63) g/l for IgM; 4.19 (3.38; 5.71) g/l for IgA. At week 2 of TCZ therapy, there was a reduction in the levels of CRP to 0.5 (0.3; 1) mg/l, IgM RF to 191.5 (45.6; 507.5) IU/ml, IgA RF to 225.8 (74.2; 547.4) IU/ml; at week 4, there were decreases in anti-MCV titers to 312.15 (81.2; 925.5) IU/ml, which remained until week 24 (p < 0.01). By week 24 of therapy, there were falls of IgG to 9.41 (8.14; 11.8) g/l, IgM to 1.12 (0.89; 1.94) g/l, IgA to 2.15 (1.73; 2.73) g/l (р < 0.01); however, their mean level as a whole remained to be in the normal range. The anti-MCV-positive patients with RA more frequently achieved a CDAI remission at week 24 than did the anti-MCV-positive patients (odd ratio, 18.4; p = 0.03). DAS 28 remission rates increased in patients with lower baseline serum IgG and IgM (p = 0.01 and 0.04, respectively). Conclusion. Thus, the analysis of the results of therapy with TCZ following 24 weeks shows that the drug is able to promptly induce steady-state positive changes in immune and inflammatory markers and to cause a drop in autoantibody titers and immunoglobulins in patients with RA. Anti-MCV-seropositivity and lower baseline serum IgG and IgM levels can be considered as possible predictors of remission at 24 weeks of the therapy.